The Influence of Attitude and Need for Cognition on Student's Purchase Intention Behavior on Halal Food: Schools Clustering Perspective - Indrawan, Boby; Nurmita, Nurmita; Nengsih, Titin Agustin; Utami, Wiji; Nasrudin, Dindin; Tanti, Tanti; Deliza, Deliza; Ferawati, Rofiqoh; Syafitri, Rita; Santoso, Pugoh (UIN Sunan Gunung Djati Bandung, 2022)
The halal food study is one of the prominent research fields in halal trends. Currently, the halal food concept is not only the worship of Muslims to Allah, but also this concept is adopted by non-Muslim with healthy lifestyle considerations. Therefore, the insight of the influenced variable on purchased intention behavior of students is crucial to research as basic information for all stakeholders, such as the seller, marketer, policymaker, government, and researchers. This study aims to identify and compare the independent variables that influence the behavior of students' purchase intentions from the school's clustering perspective. A quantitative approach has investigated the influence of attitude and need for cognition (NFC) variables on students' purchase intention behavior on halal food. The self-administrated questionnaire was used to collect the data from 561 respondents and input them into the Survey123 software. The data were analyzed using descriptive and interferential statistics. The result showed that attitude toward halal (HA) and NFC were accepted as the influenced variable on halal food purchase intention behavior. Furthermore, the students from Islamic schools tend to have purchase intentions on halal than in senior high The result of this study could be strategic marketing in the halal food industry. Then, the school must strengthen halal awareness in the syllabus.